The The Enzalutamide and EPI-001 Modulate Cell Proliferation and Metastasis Markers in T47D by Targeting AR/ARV7 - Belal M Ali; Hanan S El-Abhar; Dalaal M Abdallah; Ghada Mohamed; Marwa Sharaky; Samia A. Shouman; Marwa Kamel (Indonesian Journal of Pharmacy, 2023)
Androgen receptor (AR) and its splicing variant 7 (ARv7) play vital roles in the pathobiology of breast cancer (BC) but their role in the estrogen receptor-positive (ER+) type is controversial. Hence, we studied the influence of the blockers of AR (Enzalutamide) and ARv7 (EPI-001) on tumorigenesis processes using T47D, an ER+ BC cell line. Several techniques were employed: Sulphorhodamine assay (SRB), Flow cytometry, Immunostaining, Scratch wound healing assay, Enzyme Linked Immunosorbent assay (ELISA), and Western blot. Mechanistically, the drugs successfully arrested the cell cycle at S-phase and downregulated the protein expression of cyclins A, E, & C. Additionally, they inhibited the cell proliferation stimulator nuclear factor kappa B (NF-ĸB), whereas only EPI-001 reduced the cell regulatory marker c-Myc. They also opposed the endothelial-to-mesenchymal transition (EMT) process, by boosting the epithelial marker E-cadherin and reducing the protein expression of the mesenchymal marker fibronectin. Their anti-metastatic potential was evidenced by the hindrance of cell migration using the wound healing assay and further confirmed by the downregulation of metalloproteinase (MMP) 2 and 9 protein expression, and protein content of Rho kinase (ROCK)1 and 2. Besides, by downregulating the protein expression of vascular endothelial growth factor (VEGF) the drugs point to their anti-angiogenic aptitude. In conclusion, this in-vitro study highlights the importance of targeting AR/ARv7 using Enzalutamide and EPI-001 in decreasing proliferation cell markers, EMT, and metastasis in ER+ BC cells, findings that may have great impact in the treatment of ER+ BC.